(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
The performance of Al-Maameera wastewater treatment plant was studied according to some parameters from August2020 to June 2021.The evaluation was Temperature(Temp.),pH, Total Suspended Solids(TSS), Nitite(NO2), Nitrate(NO3), Ammonia(NH3), Phosphate(PO4), Biological Oxygen Demand(BOD), Chemical Oxygen Demand(COD), Oil & Grease(O&G), Hydrogen Sulfide(H2S) ,Sulphate(SO4) and Chlorides(Cl).The Result showed was good removal efficiency for TSS, BOD, COD, O&G and H2S, where the wastewater treatment plant was low in removal efficiency for another parameters. Finally the wastewater treatment plant is inefficient in removing some important pollutants.